Site-Specific Art Installation: Ruang Masuk ArtJog “Arts in Common” di Jogja National Museum - Elfandi, Amy; Kurniawan, Harry (ATRIUM: Jurnal Arsitektur, 2025)
Title: Site-Specific Art Installation; Entrance of ArtJog “Arts in Common” at Jogja National Museum The art installation serves as an object that fills a space in a building, an imaginary space, or a space in the open air. The installation possesses aesthetic characteristics that defy rigid boundaries in fine art, which are typically considered standard, and it also lacks limitations in the use of media or materials. ArtJog is one of the premier art exhibition events in Yogyakarta, featuring art installations. ArtJog originated from art fairs that always featured a central art installation placed at the entrance, using a concept or theme in line with the ongoing exhibition. ArtJog art installations are non-permanent, so that the exhibition space will be dismantled upon the exhibition's conclusion. The main art installation work at the entrance is essential as an application of the concept and theme that means "there is an ArtJog exhibition" with the function of the workspace in it, as well as being a connecting space between the outside space and the space in the gallery which can be formulated as site-specific art. The elements of site-specific art can be articulated and defined as a special relationship between objects or events and their specific locations. This study will examine the three years of ArtJog to identify the theoretical elements of site-specific art, focusing on the central art installations of ArtJog in 2019, which marked the beginning of the overarching theme "Arts-in-Common", the second year, 2021, and the third year, 2022. The study will conclude by analysing the characteristics of site-specific art.